Trabalho social com famílias: discursos proferidos pelos profissionais do Centro de Referência da Assistência Social - Costa, Rafaela Rocha da Costa (2015)
The general objective of this dissertation is to analyze the discourses on family cast by Psychologists Social Workers and working in CRAS João Pessoa-PB and the effects of meaning produced in practice. The specific goals are: To characterize the training of professionals to work with families; To analyze discursively constructed meanings about family for these professionals; To identify the use of discourses on family institutionalized in the Social Assistance Policy; To describe the actions that have been developed with families; identify the Coexistence Services and Strengthen Links of accompanied by CRAS; And analyze the relation between the discourses and practices in CRAS. It was used documents, quizzes, open interviews and field journal. Proceeded to content analysis, frequency counts and Critical Discourse Analysis based on the writings of Foucault also theoretical basis of the dissertation. Was analyzed seven reports, 36 participants completed the questionnaire and ten to the interview. Most are women, no gazetted and service time ranging from two weeks to eight years. The actions developed with families more often are isolated and bureaucratic. The subjectivation was analyzed from the motivation face of difficulties and conformist speech. The regular event that marked the history of how they learned about family was professional practice, said the theory differs from practice. Regular speeches are from nuclear and dysfunctional family. Have spoken contradictory speeches, talking about the guarantee of rights, but of welfare practices, hygienists and control, occupying the place of power and knowledge. Front of the supported actions in practice and common sense, it is concluded that social issues have still been pathologized in working with families.